The importance of Islamic literature curriculum: A perspective study on its relevance to contemporary society - Hj. Yaakub, Muhamadul Bakir; Taha Idris, Musa Saeed (2013)
This study is an attempt to presents a brief introductory about Islamic literature and to highlight the importance of this type of literature been incorporated within contemporary educational system.